2002
DOI: 10.1073/pnas.062181799
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 transcriptionally regulates genes involved in breast tumorigenesis

Abstract: Loss of function of BRCA1 caused by inherited mutation and tissuespecific somatic mutation leads to breast and ovarian cancer. Nearly all BRCA1 germ-line mutations involve truncation or loss of the C-terminal BRCT transcriptional activation domain, suggesting that transcriptional regulation is a critical function of the wild-type gene. The purpose of this project was to determine whether there is a link between the role of BRCA1 in transcriptional regulation and its role in tumor suppression. We developed a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
2
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(185 citation statements)
references
References 59 publications
(61 reference statements)
7
173
2
3
Order By: Relevance
“…Previous research has shown that BRCA1 protein increases arrest in the cell cycle progression of cells [24]. In addition, BRCA1 protein is reported to indicate the positively regulated expression of CCND1 [25], PCNA [26], NEK2 [27] and MAD2L1 [28]. In the present cell system, cell cycle-related genes, especially those participating in this genetic network (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Previous research has shown that BRCA1 protein increases arrest in the cell cycle progression of cells [24]. In addition, BRCA1 protein is reported to indicate the positively regulated expression of CCND1 [25], PCNA [26], NEK2 [27] and MAD2L1 [28]. In the present cell system, cell cycle-related genes, especially those participating in this genetic network (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…32,82,83 BRCA1 gene promoter is methylated in 460% of medullary 95,96 and metaplastic 32 breast cancers of basal-like phenotype. Sporadic invasive ductal carcinomas with basal-like phenotype express ID4, a negative regulator of BRCA1, 97,98 at significantly higher levels than grade-matched controls. 32 This mechanism may account for the low levels of BRCA1 expression in sporadic basal-like carcinomas of ductal morphology.…”
Section: S Badve Et Almentioning
confidence: 94%
“…In that study, and in a study by Bouras et al (2002), high levels of STC1 expression were found to be associated with estrogen receptor positivity, which is a marker of good prognosis. Furthermore, the tumor suppressors BRCA1 and p53 have both been reported to upregulate STC1 gene expression (Welcsh et al, 2002;Lai et al, 2007). Continued expression of these genes in cancers is usually associated with good prognosis, and this may be explained in part by STC1 acting as a downstream mediator of apoptosis.…”
Section: Regulation Of Oxidative Stress Response By Stc1mentioning
confidence: 99%
“…A number of studies, mostly correlative, of mammalian STC1 mRNA and protein expression have ascribed roles to STC1 ranging from angiogenesis (Kahn et al, 2000;Bell et al, 2001), bone and muscle development (Jiang et al, 2000;Filvaroff et al, 2002;Varghese et al, 2002;Yoshiko et al, 2003), inflammation (Iyer et al, 1999;Kanellis et al, 2003), cellular metabolism (McCudden et al, 2002;Ellard et al, 2007) and cancer (Fujiwara et al, 2000;Ismail et al, 2000;Okabe et al, 2001;Welcsh et al, 2002). Establishing the functional importance and relevance of these putative functions has proved difficult; moreover, STC1-null mice housed in standard laboratory conditions have no obvious phenotype (Chang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation